Pre-reproductive maternal enrichment influences offspring developmental trajectories: motor behavior and neurotrophin expression - Caporali, Paola; Cutuli, Debora; Gelfo, Francesca; Laricchiuta, Daniela; Foti, Francesca; De Bartolo, Paola; Mancini, Laura; Angelucci, Francesco; Petrosini, Laura (Frontiers in Behavioral Neuroscience, 2014)
Environmental enrichment is usually applied immediately after weaning or in adulthood, with strong effects on CNS anatomy and behavior. To examine the hypothesis that a pre-reproductive environmental enrichment of females could affect the motor development of their offspring, female rats were reared in an enriched environment from weaning to sexual maturity, while other female rats used as controls were reared under standard conditions. Following mating with standard-reared males, all females were housed individually. To evaluate the eventual transgenerational influence of positive pre-reproductive maternal experiences, postural and motor development of male pups was analyzed from birth to weaning. Moreover, expression of Brain Derived Neurotrophic Factor and Nerve Growth Factor in different brain regions was evaluated at birth and weaning. Pre-reproductive environmental enrichment of females affected the offspring motor development, as indicated by the earlier acquisition of complex motor abilities displayed by the pups of enriched females. The earlier acquisition of motor abilities was associated with enhanced neurotrophin levels in striatum and cerebellum. In conclusion, maternal positive experiences were transgenerationally transmitted, and influenced offspring phenotype at both behavioral and biochemical levels.